Effect of Arbuscular Mycorrhizal Fungi on Growth of Groundnut and Disease caused by Macrophomina phaseolina. - Doley, K; Jite, P.K (Journal of Experimental Sciences, 2013)
Efficacy of arbuscular mycorrhizal fungi (AMF) was evaluated for the biological control of soil-borne plant pathogen Macrophomina phaseolina in groundnut plant. For this investigation pot culture technique was followed. Soil based mixture of AM fungi (Glomus fasciculatum) was inoculated onto the root of groundnut. In results the colonization by mycorrhizal fungi significantly resulted into decreased incidence of disease caused by M. phaseolina. The growth of groundnut showed marked increase due to mycorrhizal colonization viz. shoot and root length, fresh and dry weight, leaf, nodule and pod number. In presence of pathogen mycorrhizal dependency was significantly higher but degree of colonization went down. The content of chlorophyll was found to be increased significantly due to inoculation of AM fungi. The various bio-chemical and defense related enzyme activities were investigated and the results obtained showed significant increase in their activities due to pathogen as well as AM fungi inoculation. But, highest activities were recorded where both pathogen as well AM fungi were involved. Thus, inoculation of AM fungi showed great bio-control ability as well as growth promoter. Moreover, it showed their efficacy in inhibition of damaging effect caused by pathogen M. phaseolina.